ADVENT OF TECHNOLOGY AND ITS EFFECT ON CHANGING TEACHING SCENARIO - Ms. Apurva Goyal1, Mr. Puneet Kumar2 (International journal of economic perspectives, 2023)
With the Covid-19 pandemic affecting people and overall economic activities around the world, technology is now more significant than ever and is also becoming a new reality for learning and teaching processes. Technology has played a major role in bringing people back from the lockdown scenarios disrupting academics.Distances are no longer an impediment to education, and it is now available to students on a daily basis. Today, more than ever, educational institutions are engaging virtually with teachers and students with use of Information and Communication technologies (ICTs). It is now being referred to as educational technology (EduTech). The major role that education technology plays is improving communication among peers, which facilitates the transfer of skills and knowledge to students and also improves the quality of study time.